The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1159/000262319
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Bone Mineral Density in Sickle Cell Disease Patients with the High-Hb F Phenotype

Abstract: Low bone mineral density (BMD) is common in sickle cell disease (SCD) patients of all ages due to erythropoietic stress and consequent bone marrow hyperplasia. Kuwaiti SCD patients have a mild clinical phenotype because of their high Hb F level. There has been no previous documentation of BMD in this population of patients. SCD patients (n = 81) and controls (n = 67) were recruited from hematology clinics of Mubarak Hospital, Kuwait. BMD was measured using dual X-ray absorptiometry (Hologic) in the lumbar spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…These results are accompanied by a significant reduction in PTH and serum Ca concentrations and increased concentration of bone turnover parameters (OC, b-ALP and CTX). These results are in accordance with those of previous literature [1, 23], and suggest a relation between low BMD and increased bone turnover, as previously reported [24]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are accompanied by a significant reduction in PTH and serum Ca concentrations and increased concentration of bone turnover parameters (OC, b-ALP and CTX). These results are in accordance with those of previous literature [1, 23], and suggest a relation between low BMD and increased bone turnover, as previously reported [24]. …”
Section: Discussionsupporting
confidence: 94%
“…Sickle-cell disease (SCD) is an autosomal recessive genetic disease with an increase in the adhesion of sickled erythrocytes, and it is a potential cause of vaso-occlusive episodes, which are related to clinical manifestations, morbidity and mortality [1, 2]. The SCA often coincides with osteoporosis or osteopenia in children and young adults [3].…”
Section: Introductionmentioning
confidence: 99%
“…The infarction of vertebral bone marrow and the presence of osteoporosis may produce collapse of the vertebrae with the typical fish mouth appearance. Several studies have shown an overall reduction in BMD in children and adults with SCD (9,(12)(13)(14). In recent studies, according to WHO criteria, 70-80% of SCD patients were osteoporotic or osteopenic (15)(16)(17).…”
Section: Sickle Cell Disease and The Bonesmentioning
confidence: 99%
“…However, the unreliable interpretations of DXA results have led to numerous misdiagnoses due to overestimating and underestimating BMD levels in general [Gafni and Baron, 2004; Wren et al, 2005]. Additionally, variations in the BMD of sickle patients are based on age, gender, and ethnicity, further minimizing the usefulness of BMD to monitor sickle bone by itself [Almedia and Roberts, 2005; Gupta et al, 2009; Lal et al, 2006; Sarrai et al, 2007]. …”
Section: Introductionmentioning
confidence: 99%